Polymorphisms in the genes of citohrom oxidase P450 2D6 (CYP2D6), paraoxonase 1 (PON1) and apolipoproteine E (APOE) as risk factors for Parkinson's disease - Đurić Gordana; Svetel Marina; Illarioškin Nikolaevič Sergej; Dragađević Nataša; Gavrilović Jelena; Kostić Vladimir S. (Vojnosanitetski Pregled)
Background/Aim. The presence of Parkinson's disease (PD) among the members of a family is a clear indication of the significance of genetics in its development. In spite of that, the majority of patients with PD shows a sporadic form of the disease induced as a result of interaction of both environmental and genetic factors. The aim of this study was to examine the effects of polymorphisms in the genes of cytohrome P450 2D6(CYP2D6), paraoxonase 1 (PON 1) and apolipoprotein E (APOE), as risk factors for PD. Methods. We examined 106 patients with PD (65 men and 41 women) and 75 ethnically matched control subjects. The mean age at onset of PD in the patients was 46.9±9.4 years (ranging from 30 to 70 years). Genotyping was performed using standard PCR amplification and restriction endonuclease digestion protocols described for known polymorphism in the candidate genes under study. Results. The genotype A/A polymorphisms 2D6* gene of CYP2D6 and genotype M/M polymorphisms L54M gene of PON1 were significantly more frequent in the patients with PD than in the control group. The patients with genotypes A/A and M/M had 3.4 and 3.2 higher risk of PD, respectively than the control group (p = 0.01). The relation between genotypes A/A gene of CYP2D6 and M/M gene of PON1 was modified by the age at onset. The genotypes were associated with early onset of PD (p = 0.001, p = 0.004). The carriers of the A and M alleles in homozygote had 2.4 and 4.2 years respectively earlier onset of PD than carriers of other genotypes with these polymorphisms. The frequency allele ε4 gene of APOE was higher in the PD patients with early onset (20%) than in PD with later onset (7.4%), while the genotype ε3/ε3 was associated with PD late onset (p = 0.024). Combined genotype I (carriers of the two risk allels in homozygote and one alleles risk in heterozygote) and combined genotype II (carriers of the three alleles risk in homozygote) caused early PD. Combined genotype II was detected in 12.7% of the patients in the group of early onset, and in 2.4% of the patients with the onset after 45 years. Conclusion. The results of our study suggest that the genotypes A/A and M/M genes of CYP2D6 and PON1, and allele ε4 gene are an important risk for the development of PD, causing its early onset. The cumulative effects of the risk genes cause an early onset of PD.